2022
DOI: 10.1371/journal.pgph.0000071
|View full text |Cite
|
Sign up to set email alerts
|

Malaria prevalence, knowledge and associated factors among household heads in Maygaba town, Ethiopia

Abstract: Malaria remains a leading public health issue in Ethiopia, despite wide use of insecticide-treated mosquito nets (ITNs). Consistent use of ITNs reduces malaria transmission by 90%. However, coverage and proper use of ITNs are the major challenge for most rural settings of Ethiopia. We assessed the prevalence of malaria, ITNs use and associated factors among household heads in Maygaba town, northwest Ethiopia. A cross-sectional study was carried out among 403 households using a structured questionnaire. Blood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
(64 reference statements)
2
3
0
Order By: Relevance
“…For the majority of women in both study groups, pregnant women and young children were identified as the most vulnerable populations in need of priority attention for malaria prevention. This is aligned with a study conducted in Ethiopia which reported that the population understood the importance of protecting children and pregnant women [15]. As in a similar study conducted in Madagascar, we found that 50% of the women in our study felt that other vulnerable groups living around them should be equally protected [16].…”
Section: Discussionsupporting
confidence: 92%
“…For the majority of women in both study groups, pregnant women and young children were identified as the most vulnerable populations in need of priority attention for malaria prevention. This is aligned with a study conducted in Ethiopia which reported that the population understood the importance of protecting children and pregnant women [15]. As in a similar study conducted in Madagascar, we found that 50% of the women in our study felt that other vulnerable groups living around them should be equally protected [16].…”
Section: Discussionsupporting
confidence: 92%
“…The results indicate that participants who had received health information about malaria were less likely to have malaria than those who had not, with a COR of 1.78 and a 95% CI of 1.04-3.04. This evidence supported by study done in different part of Ethiopia (31). This suggests that health information about malaria may have a protective effect against malaria infection.…”
Section: Discussionsupporting
confidence: 75%
“…The pesticides also repel vectors, which reduces the number of insects that enter the residence and try to feed on the people’ blood (43). The malaria prevention and control programme in Ethiopia targets 100.0% household coverage with two ITNs per household in all malaria endemic areas (44). However, there is a geographical difference in the distribution of malaria and leishmaniasis in the country.…”
Section: Discussionmentioning
confidence: 99%